(untitled) (International Journal of Engineering and Computer Science, 2024)
The accelerating pace of software development, fueled by agile methodologies and continuous integration practices, has exposed the limitations of traditional Quality Assurance (QA) techniques. Manual test case design and static test data provisioning are no longer sufficient to meet the demands of modern software systems that require high reliability, rapid releases, and robust performance under varied conditions. This paper explores how Artificial Intelligence (AI) is fundamentally transforming QA workflows—particularly in the realms of test case design and test data generation. It examines the implementation of AI-driven methods such as Natural Language Processing (NLP) for automated test case derivation, predictive modeling for test prioritization, and reinforcement learning for exploratory test optimization. Additionally, it investigates the application of advanced AI techniques like constraint-solving, Generative Adversarial Networks (GANs), and AI-powered fuzzing for dynamic and intelligent test data generation. A comparative analysis between conventional QA practices and AI-augmented approaches is presented, using real-world benchmarks and metrics including test coverage, execution time, defect detection rate, and required human involvement. The results demonstrate significant improvements in efficiency, scalability, and defect discovery when AI technologies are employed. Despite evident advantages, the paper also acknowledges challenges such as model explainability, integration with legacy systems, and the need for quality training data. Finally, it provides a forward-looking perspective on how AI will continue to evolve QA practices, paving the way for self-healing automation, autonomous QA agents, and intelligent quality analytics. This research offers a foundational understanding for developers, testers, and QA strategists aiming to integrate AI into their quality assurance ecosystems.